Media Informasi Website pada Wisata Kuliner Panganan Khas Mandar - Dian Megah Sari; Asmawati S. (Teknik Informatika Universitas Pamulang, 2020)
Limited information on typical Mandar culinary in Majene Regency, such as types of food, location of food, operating hours, and transportation are references to provide complete information to tourists. Information about typical Mandar food requires the role of technology in it, considering that it plays a very important role in helping tourists or local people to find information about Mandar specialties, it is requires a media capable of providing information about the address of the place to eat, the type of food served, the hours of operation, and transportation used. The purpose of this research is to design website information media on Mandar culinery touris in Majene regency that can help tourist or local communities. Based on a series of research it can be conclude that the website information media on typical Mandar culinary tours in Majene Regency can make it easy for tourist or local people to get information about the Mandar culinary tours and decide which restaurant wiil they choice.